Seven day insertion rest in whole body vibration improves multi-level bone quality in tail suspension rats. - Rui Zhang (Public Library of Science (PLoS), 2014)
Objective This study aimed to investigate the effects of low-magnitude, high-frequency vibration with rest days on bone quality at multiple levels. Methods Forty-nine three-month-old male Wistar rats were randomly divided into seven groups, namely, vibrational loading for X day followed by X day rest (VLXR, X = 1, 3, 5, 7), vibrational loading every day (VLNR), tail suspension (SPD), and baseline control (BCL). One week after tail suspension, rats were loaded by vibrational loading (35 Hz, 0.25 g, 15 min/day) except SPD and BCL. Fluorescence markers were used in all rats. Eight weeks later, femora were harvested to investigate macromechanical properties, and micro-computed tomography scanning and fluorescence test were used to evaluate microarchitecture and bone growth rate. Atomic force microscopy analyses and nanoindentation test were used to analyze the nanostructure and mechanical properties of bone material, respectively. Inductively coupled plasma optical emission spectroscopy was used for quantitative chemical analyses. Results Microarchitecture, mineral apposition rate and bone formation rate and macromechanical properties were improved in VL7R. Grain size and roughness were significantly different among all groups. No statistical difference was found for the mechanical properties of the bone material, and the chemical composition of all groups was almost similar. Conclusions Low-magnitude, high-frequency vibration with rest days altered bone microarchitecture and macro-biomechanical properties, and VL7R was more efficacious in improving bone loss caused by mechanical disuse, which provided theoretical basis and explored the mechanisms of vibration for improving bone quality in clinics.